2022
DOI: 10.3390/s22030847
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Localization Using Doppler Shift and Time of Arrival Measurements in a Tunnel Environment

Abstract: Most applications and services of Cooperative Intelligent Transport Systems (C-ITS) rely on accurate and continuous vehicle location information. The traditional localization method based on the Global Navigation Satellite System (GNSS) is the most commonly used. However, it does not provide reliable, continuous, and accurate positioning in all scenarios, such as tunnels. Therefore, in this work, we present an algorithm that exploits the existing Vehicle-to-Infrastructure (V2I) communication channel that opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 59 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the authors observed a relationship between vehicle velocity and range and they explain it as a consequence of the Doppler effect. This can also be observed in [13]. The inverse case is, however, observed in [14], where the OD is greater than the ID; however, the authors explain that this is due to the time needed for the mechanism of signal validation in the Wi-Fi access points during a first connection.…”
Section: Anomaly Detectionmentioning
confidence: 94%
“…Moreover, the authors observed a relationship between vehicle velocity and range and they explain it as a consequence of the Doppler effect. This can also be observed in [13]. The inverse case is, however, observed in [14], where the OD is greater than the ID; however, the authors explain that this is due to the time needed for the mechanism of signal validation in the Wi-Fi access points during a first connection.…”
Section: Anomaly Detectionmentioning
confidence: 94%
“…Subsequently, its neighbors can build a positioning table of the neighboring nodes [28]. The second approach depends on the physical parameters such as received signal strength (RSS) [29], angle of arrival (AoA) [30], and time of arrival (ToA) [31] in obtaining the jammer location. These RSS-based solutions achieve quite a low accuracy in estimating the jammer's position.…”
Section: B Localizationmentioning
confidence: 99%